The effect of galo-galo honey extract (heterotrigona itama) on the formation of pseudomonas aeruginosa biofilm: study experimental - Julianingsih, Wulan; Amly, Dina Auliya; Ferdina, Resa (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2025)
ABSTRACTIntroduction: Pseudomonas aeruginosa is a Gram-negative bacterium resistant to antibiofilm agents and a major pathogen responsible for nosocomial infections. This can be prevented with chlorhexidine; however, this substance may cause oral irritation. One natural alternative is Galo-galo bee honey (Heterotrigona itama), which contains various antibiofilm components, including fructose, hydrogen peroxide, and flavonoids. This study aims to analyze the effect of Galo-galo bee honey extract on the biofilm formation of Pseudomonas aeruginosa. Methods: The research was conducted using an experimental method. The Galo-galo bee honey extract was obtained through centrifugation, and the supernatant was then used for antibiofilm activity testing, measuring absorbance at 540 nm (λ 540 nm). Parametric statistical analysis using ANOVA Welch indicated significant differences in the inhibitory effects on biofilm formation of Pseudomonas aeruginosa among the treatment groups with different concentrations of Galo-galo bee honey extract (p<0.05). Post hoc Games Howell tests revealed no significant difference (p>0.05) between the 0.09% concentration and the 0.19% and 0.39% concentrations. Results: Significant increases (p<0.05) were identified at concentrations of 6.25%, 3.125%, 1.56%, and 0.78% compared to concentrations ≤ 0.39%. Other significant increases were also found at concentrations of 50%, 25%, and 12.5% compared to concentrations ≤ 6.25%, with further significant differences (p<0.05) observed between the 50% concentration and both the 25% and 12.5% concentrations, as well as between the 25% and 12.5% concentrations. Conclusion: There is a difference effect of Galo-galo bee honey extract on the formation of Pseudomonas aeruginosa biofilm. Higher concentrations of Galo-galo bee honey extract are more effective in inhibiting biofilm formation by Pseudomonas aeruginosaKEY WORDS: Antibiofilm, Galo-galo bee honey (Heterotrigona itama), Pseudomonas aeruginosa.Perbedaan efek ekstrak madu lebah galo-galo (heterotrigona itama) terhadap pembentukan biofilm pseudomonas aeruginosa: Studi eksperimentalABSTRAKPendahuluan: Pseudomonas aeruginosa merupakan bakteri Gram-negatif yang resisten terhadap antibiofilm dan patogen utama penyebab infeksi nosokomial. Hal ini dapat dicegah dengan chlorhexidine tetapi bahan ini dapat menyebabkan iritasi mulut. Salah satu bahan alternatif adalah madu lebah Galo-galo (Heterotrigona itama) memiliki berbagai kandungan antibiofilm, yaitu fruktosa, hidrogen peroksida dan flavonoid. Penelitian ini bertujuan untuk mengetahui pengaruh ekstrak madu lebah Galo-galo (Heterotrigona itama) terhadap pembentukan biofilm Pseudomonas aeruginosa. Metode: Penelitian ini dilakukan dengan metode eksperimental. Ekstrak madu lebah Galo-galo (Heterotrigona itama) diperoleh dengan cara disentrifugasi lalu diambil supernatannya kemudian dilakukan uji aktivitas antibiofilm dan diukur absorbansinya (λ 540 nm). Analisis statistik parametrik ANOVA Welch menunjukkan bahwa terdapat perbedaan efek hambat pembentukan biofilm Pseudomonas aeruginosa yang signifikan (p<0,05) diantara kelompok perlakuan konsentrasi ekstrak madu lebah Galo-galo (Heterotrigona itama). Uji post hoc Games Howell menunjukkan bahwa tidak ada perbedaan signifikan (p>0,05) antara konsentrasi 0,09% dengan konsentrasi, 0,19%, dan 0,39%. Results: Peningkatan signifikan (p<0,05) teridentifikasi pada konsentrasi 6,25%, 3,125%, 1,56%, dan 0,78% dengan konsentrasi ≤ 0,39%. Peningkatan signifikan antibiofilm yang lainnya juga ditemui pada konsentrasi 50%, 25%, dan 12,5% dengan konsentrasi ≤ 6,25, lebih lanjut perbedaan yang signifikan (p<0,05) juga ditemui antara konsentrasi 50% dengan 25% dan 12,5%, serta konsentrasi 25% dengan 12,5%. Simpulan: terdapat perbedaan efek ekstrak madu lebah Galo-galo (Heterotrigona itama) terhadap pembentukan biofilm Pseudomonas aeruginosa. Semakin tinggi konsentrasi ekstrak madu lebah Galo-galo (Heterotrigona itama) maka semakin efektif dalam menghambat pembentukan biofilm Pseudomonas aeruginosa.KATA KUNCI: Madu lebah Galo-galo (Heterotrigona itama), antibiofilm, Pseudomonas aeruginosa.